ANALISIS IMPLEMENTASI KEBIJAKAN PERCEPATAN PENURUNAN STUNTING DI KELURAHAN TANJUNG MAS, KECAMATAN SEMARANG UTARA, KOTA SEMARANG - Nadia Nurmala Mukti; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study is motivated by the stunting rate in Semarang City that remains far below the national target, particularly in Tanjung Mas Sub-district, which frequently falls into the red zone (>200 cases) each year. This study aims to analyze the conformity of stunting reduction policy implementation based on Semarang Mayor Regulation Number 45 of 2023, as well as to identify its supporting and inhibiting factors. The method employed is descriptive qualitative, with data collected through in-depth interviews with cadres, midwives, and sub-district officials, direct observation of posyandu activities and stunting programs in the field, and documentation of relevant policy documents and activity reports. The results indicate that of the five policy pillars, the fourth pillar concerning household and community food and nutrition security has not been optimally implemented due to public misconceptions about stunting. Of the six strategies, only the first strategy related to iron-folic acid tablet consumption among pregnant women has been properly implemented, while the remaining five strategies are still hindered by low participation, limited understanding, and infrastructure constraints. Supporting factors include the communication aspect, characterized by effective socialization and routine coordination, and the bureaucratic structure aspect, marked by clear regulations and orderly division of tasks. Inhibiting factors stem from the resource aspect, namely unequal posyandu facilities across areas due to dependence on unevenly distributed CSR funding, and the implementor attitude aspect, reflected in the declining commitment of some cadres due to limited regeneration and slow responsiveness to sanitation infrastructure assistance requests. It is concluded that policy implementation has not been fully optimal on the beneficiary side. It is recommended that the sub-district government strengthen community-based education, equalize resource distribution, accelerate cadre regeneration, and improve responsiveness to sanitation infrastructure assistance requests.